Empowering Neurodivergent Learners: Developing Inclusive Learning Technologies Based on Cognitive Behavioral Theories - Seo Jiwon; Nguyen Tuan Anh; Shahinur Rahman (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. The effectiveness of inclusive learning technologies for neurodivergent learners is strongly influenced by how well these tools align with cognitive and behavioral needs. Cognitive Behavioral Theories (CBT) provide a structured framework for addressing learning barriers by focusing on thought patterns, emotional regulation, and adaptive behaviors. Purpose. This study aimed to investigate the development and evaluation of inclusive learning technologies grounded in CBT frameworks. Specifically, it examined how these technologies can empower neurodivergent learners—such as those with autism spectrum disorder (ASD), ADHD, and dyslexia—by improving focus, self-regulation, and active participation in the learning process. Method. The research employed a mixed-methods approach involving 220 neurodivergent learners across higher education and special education settings. Quantitative data were collected through pre- and post-intervention surveys measuring cognitive engagement, emotional regulation, and perceived inclusivity. Results. The findings indicate that CBT-informed digital tools significantly enhanced self-monitoring, reduced task-related anxiety, and increased collaborative engagement across diverse learning contexts. Learners with ADHD showed marked improvements in task persistence, while those with dyslexia demonstrated better comprehension outcomes when adaptive text and cognitive scaffolding features were included. Conclusion. This study highlights the transformative role of CBT-based inclusive technologies in empowering neurodivergent learners. By embedding cognitive-behavioral strategies into digital learning platforms, educators can design interventions that promote equity, resilience, and sustainable learning outcomes. The results carry important implications for future policy, curriculum design, and educational technology innovation aimed at inclusive education.